2021
DOI: 10.3847/1538-4357/ac256f
|View full text |Cite
|
Sign up to set email alerts
|

Probing Current Sheet Instabilities from Flare Ribbon Dynamics

Abstract: The presence of current sheet instabilities, such as the tearing mode instability, are needed to account for the observed rate of energy release in solar flares. Insights into these current sheet dynamics can be revealed by the behavior of flare ribbon substructure, as magnetic reconnection accelerates particles down newly reconnected field lines into the chromosphere to mark the flare footpoints. Behavior in the ribbons can therefore be used to probe processes occurring in the current sheet. In this study, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…However, which comes first remains a major open question. French et al (2021) found evidence supporting the development of the tearing mode instability prior to the increase in excess line broadening followed by a rapid increase in line broadening and evolution of the energy spectrum in accordance with a turbulencedominated regime, something supported by simulations (Dong et al 2018;Tenerani & Velli 2020). For the events studied here, we observe a gradual increase in line broadening followed by a rapid increase coincident with the drop in free magnetic energy for the first X-class flare and a coincident increase in line broadening and a decrease in free magnetic energy for the second.…”
Section: Isotropic Turbulencementioning
confidence: 99%
“…However, which comes first remains a major open question. French et al (2021) found evidence supporting the development of the tearing mode instability prior to the increase in excess line broadening followed by a rapid increase in line broadening and evolution of the energy spectrum in accordance with a turbulencedominated regime, something supported by simulations (Dong et al 2018;Tenerani & Velli 2020). For the events studied here, we observe a gradual increase in line broadening followed by a rapid increase coincident with the drop in free magnetic energy for the first X-class flare and a coincident increase in line broadening and a decrease in free magnetic energy for the second.…”
Section: Isotropic Turbulencementioning
confidence: 99%
“…Jing et al (2016) used exceptionally high resolution H images from the Visible Imaging Spectrometer installed at the Goode Solar Telescope (GST, Goode and Cao 2012) in BBSO to measure the fine structures (below 500 km) of flares, which may reflect the complex structure of the reconnecting current sheet. French et al (2021) analyzed the highcadence (1.7 s) data of the Interface Region Imaging Spectrograph (IRIS) slit Jaw Fig. 15 Unusual hard X-ray ribbons.…”
Section: Structure Along Ribbon Axis As 2d Processmentioning
confidence: 99%
“…Another interesting example comes from French et al (2021), who used high-cadence IRIS slit jaw images to examine the growth of the intensity in flare ribbons at different spatial scales in a B class flare that occurred on 2016 December 6. In this study, the intensity along the ribbon is used to calculate a fast Fourier transform (FFT), resulting in a power spectrum in the spatial domain for each time.…”
Section: Flare Ribbon Observationsmentioning
confidence: 99%